A COMPREHENSIVE REVIEW OF CAR-T CELL THERAPY ACROSS RHEUMATIC DISEASES - Mateusz Miluski; Dorota Szydłowska; Mikołaj Jońca; Natasza Kurys; Adam Kubisa; Aleksandra Dybcio; Szymon Paruszewski; Julia Kupczak; Mikhail Kazachok; Katarzyna Kupczyk (International Journal of Innovative Technologies in Social Science, 2026)
Background: Autoimmune rheumatic diseases (ARDs) are characterized by a failure of immune tolerance, leading to chronic inflammation, autoantibody production, and progressive organ damage. Conventional therapies often fail to induce long-term, drug-free remission in refractory patients. Chimeric antigen receptor (CAR) T-cell therapy, originally developed for hematological malignancies, has appeared as a promising strategy to achieve the sustained depletion of pathogenic immune cells in rheumatology. Objective: This review critically synthesizes current evidence regarding the pathophysiological mechanisms, molecular designs, clinical efficacy, and toxicity profiles of CAR-T therapy across systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), systemic sclerosis (SSc), idiopathic inflammatory myopathies (IIM), and adult-onset Still's disease (AOSD). Methods: 77 peer-reviewed sources, including clinical trials, preclinical models, and case series, were analyzed and objectively categorized by target antigens, cellular modifications, and clinical endpoints. Results: CD19-directed CAR-T cells successfully penetrate inflamed tissues and deplete the autoreactive B-cell compartment, resulting in measurable clinical remission in highly refractory SLE, SSc, and IIM cohorts.This enables the complete discontinuation of concurrent immunosuppressive drugs. Due to a complex, hypoxic synovial microenvironment, targeted RA treatment needs advanced approaches, such as fourth-generation CARs and in vivo generation techniques. Therapy-associated toxicities, primarily cytokine release syndrome (CRS) and immune effector cell-associated neurotoxicity syndrome (ICANS), generally present with significantly lower clinical severity in ARD patients compared to heavily pre-treated oncological cohorts. Conclusion: CAR-T cell therapy represents a fundamental paradigm shift in the management of severe ARD, shifting the objective from chronic immunosuppression to definitive immune reconstitution. Despite logistical, financial, and safety challenges, clinical efficacy in treatment-refractory cases remains exceptionally high.